Implementation Of The Principal's Leadership Role In Improving The Effectiveness Of School Administrative Staff Performance - Widiyanti, Ainurrohma; Supriyanto, Achmad; Kusumaningrum, Desi Eri (Proceedings Series of Educational Studies, 2025)
The role of the principal as an education manager is needed to support the effective and efficient running of the education process in the school. Leadership is the activity of managing other people as subordinates. Leadership is seen as a trigger for various activities, processes, and willingness to change the point of view or physical mentality of a group of people, both in formal and informal organizational relationships. The effectiveness of school administration personnel needs to be assessed to see the extent to which the effectiveness of school administration personnel carries out their duties and functions. This effectiveness is certainly inseparable from the leadership role of school administration personnel as managers who provide motivation, encouragement and direction to those concerned. Effectiveness is a level of success achieved by a person or group of people in a certain way in accordance with the standard goals that have been prepared. In other words, the more plans that are successfully achieved, the more effective the activity can be said to be. Good administrative staff are administrative staff who succeed can be seen through the implementation of good and consistent responsibility tasks to support the achievement of effective performance. This research uses a type of literature review research, namely looking for theoretical references that are relevant to the topic or problem specified. School administrators are an important part of the education system that has the function of supporting the continuity of school operations. School administration personnel are responsible for managing staffing, finance, student affairs, infrastructure, public relations, and curriculum activities. The result of this study is that the leadership role of the school principal is considered important to improve the effectiveness of the performance of school administrative personnel. To create a productive and efficient work environment, it is very important for school principals to exercise leadership and improve the effectiveness of school administration staff performance.